2023
DOI: 10.3390/plants12051037
|View full text |Cite
|
Sign up to set email alerts
|

Promising Application of Automated Liquid Culture System and Arbuscular Mycorrhizal Fungi for Large-Scale Micropropagation of Red Dragon Fruit

Abstract: Red dragon fruit (Hylocereus polyrhizus) is an economic and promising fruit crop in arid and semi-arid regions with water shortage. An automated liquid culture system using bioreactors is a potential tool for micropropagation and large-scale production. In this study, axillary cladode multiplication of H. polyrhizus was assessed using cladode tips and cladode segments in gelled culture versus continuous immersion air-lift bioreactors (with or without a net). Axillary multiplication using cladode segments (6.4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 36 publications
0
1
0
Order By: Relevance
“…The root growth parameters of AMF-treated blackberry plants (i.e., root length, total root length per plantlet, surface area of roots, root volume, number root tips per plantlet, and fresh and dry weights of roots) also showed a general increasing trend (Table 1). It has been previously reported that inoculation with G. margarita and G. albida significantly improved growth and root development in micropropagated plantlets of red dragon fruit (Hylocereus polyrhizus) (Dewir et al 2023a) and lacy tree philodendron (Philodendron bipinnatifidum) (Dewir et al 2023b). Supplementation of micropropagated apple plants with Glomus etunicatum, Scutellospora pellucida, Acaulospora scrobiculata, and Scutellospora heterograma led to increased plant height, shoot biomass, and root biomass (Cavallazzi et al 2007).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The root growth parameters of AMF-treated blackberry plants (i.e., root length, total root length per plantlet, surface area of roots, root volume, number root tips per plantlet, and fresh and dry weights of roots) also showed a general increasing trend (Table 1). It has been previously reported that inoculation with G. margarita and G. albida significantly improved growth and root development in micropropagated plantlets of red dragon fruit (Hylocereus polyrhizus) (Dewir et al 2023a) and lacy tree philodendron (Philodendron bipinnatifidum) (Dewir et al 2023b). Supplementation of micropropagated apple plants with Glomus etunicatum, Scutellospora pellucida, Acaulospora scrobiculata, and Scutellospora heterograma led to increased plant height, shoot biomass, and root biomass (Cavallazzi et al 2007).…”
Section: Discussionmentioning
confidence: 98%
“…Additionally, AMF protect host plants from parasites, pathogenic fungi, and nematodes by stimulating them to produce defensive compounds and increasing the area of exploration of the roots, thus increasing the flow of water from the soil to the plant, as well as by enhancing the physical and chemical properties of the soil through the addition of organic matter and formation of aggregates through the adhesion of soil particles Smith 2011a, 2011b). AMF have been successfully used to improve the acclimatization and growth of micropropagated fruit-bearing species such as walnut (Mortier et al 2020), strawberry (Taylor and Harrier 2001), pomegranate (Singh et al 2012), prunus (Monticelli et al 2000), apple (Cavallazzi et al 2007), and red dragon fruit (Dewir et al 2023a).…”
mentioning
confidence: 99%
“…In the field of agriculture, the utilization of bioreactors has seen significant growth in the production of AMF inocula. They provide a controlled environment for the mass production of AMF, which are advantageous for establishing symbiotic relationships with plant roots, facilitating nutrient uptake, and improving plant growth [7]. With the growing demand for sustainable farming practices, the utilization of AMF inocula has become increasingly crucial in contemporary agricultural systems.…”
Section: Amf Bioreactorsmentioning
confidence: 99%
“…Dietary fiber positively affects the physiology of both humans and animals. Soluble fibers, which dissolve in an aqueous solution, include pectins, mucilages, and certain types of hemicellulose and possess hypoglycemic, hypolipidemic, and hypocholesterolemic properties [ 28 ]. Insoluble fibers, which include cellulose and hemicellulose, play the role of maintaining the regulation of intestinal function, modulating peristalsis, controlling pH, and contributing to the prevention of gastrointestinal disease [ 29 ].…”
Section: Introductionmentioning
confidence: 99%